2009
DOI: 10.1093/cercor/bhn259
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Input to Distal Apical Dendrites in Neocortical Layer 1 Is Massive and Highly Convergent

Abstract: Input to apical dendritic tufts is now deemed crucial for associative learning, attention, and similar "feedback" interactions in the cerebral cortex. Excitatory input to apical tufts in neocortical layer 1 has been traditionally assumed to be predominantly cortical, as thalamic pathways directed to this layer were regarded relatively scant and diffuse. However, the sensitive tracing methods used in the present study show that, throughout the rat neocortex, large numbers (mean approximately 4500/mm(2)) of thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
180
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(191 citation statements)
references
References 70 publications
9
180
1
1
Order By: Relevance
“…5. In particular, the morphology and distribution of horizontal myelinated processes in layer I are very similar to the axons of Mtype thalamus cells [20]. Finer processes were seen more superficially, while thicker processes were seen at greater depths (Fig.…”
Section: Ocm Visualizes Cortical Myelinationmentioning
confidence: 72%
See 1 more Smart Citation
“…5. In particular, the morphology and distribution of horizontal myelinated processes in layer I are very similar to the axons of Mtype thalamus cells [20]. Finer processes were seen more superficially, while thicker processes were seen at greater depths (Fig.…”
Section: Ocm Visualizes Cortical Myelinationmentioning
confidence: 72%
“…To further illustrate this concept, Fig. 2(f) shows virtual coronal slices of different thicknesses (20,50, and 200 microns), obtained from the same volumetric OCM data set. These images could, in principle, be repeated longitudinally in the same animal over time.…”
Section: Ocm Visualizes Neuronsmentioning
confidence: 99%
“…Because thalamic relay nuclei participating in the basal ganglia and cerebellum pathways innervate different sublaminae of L5 in the frontal cortex (Jones, 2001(Jones, , 2007Kuramoto et al, 2009;RubioGarrido et al, 2009), L5 pyramidal neurons in different sublaminae likely receive differential thalamic drive. The basal ganglia and cerebellar pathways go to the rostromedial and caudolateral parts of the ventral anterior (VA) and ventral lateral (VL) thalamic nuclei (VA-VL complex), respectively, from which the former send axons to L1, while the latter project to middle cortical layers (Jones, 2001(Jones, , 2007Kuramoto et al, 2009;Rubio-Garrido et al, 2009). We found dendritic branching differences of CPn and CCS cells to be correlated with the sublaminar distributions of the thalamic inputs, suggesting that L5 pyramidal projection neurons are specialized according to their participation in corticobasal ganglia and corticocerebellar loops.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of social fear to the manipulation of the left thalamus but not the left ACC suggests a possibility that left cortical targets other than the ACC may be involved in this form of emotional learning. Recently it has been demonstrated that the anteromedial thalamic nucleus of mice is one of the few thalamic regions that have quite widespread cortical outputs (22). This suggests a possibility that the anteromedial thalamus has the potential to influence many cortical regions.…”
Section: Discussionmentioning
confidence: 99%